The STUDI WAKTU DAN OPTIMISASI DALAM PENGOLAHAN MINUMAN KOPI DENGAN KERANGKA KERJA MOST - Sabilah, Ade Irpan (Universitas Putera Batam, 2024)
Coffee beverage processing is an essential process in the rapidly growing coffee industry. From selecting coffee beans to serving customers, each processing stage plays a crucial role in determining the final quality of the coffee beverage. This study provides a deep understanding of the time aspects in the production process and lays the groundwork for improving overall production process efficiency through MOST (Maynard Operation Sequence Technique) framework analysis. The research method involves collecting data on coffee production processes from selecting coffee beans to serving customers. From the buyer's perspective, idle time reaches 260 seconds, while working time is only 105 seconds, resulting in a total time of 365 seconds. Meanwhile, from the operator's perspective, idle time is recorded at 60 seconds, with working time reaching 80 seconds, resulting in a total time of 100 seconds. From the machine's point of view, idle time is counted at 60 seconds, with working time reaching 220 seconds, resulting in a total time of 280 seconds. The research findings indicate that by applying the MOST framework, coffee beverage production time can be significantly reduced by making adjustments to several production stages, such as coffee bean grinding, coffee making process, and serving customers. These findings provide valuable insights for the coffee industry to improve production process efficiency and optimize consumer experience.